Potential Use of High Rate Algae Ponds for Resource Recovery in the Water-Food-Energy Nexus for Tanzania: A Review - Kayombo, Mary; Mayo, Aloyce W.; Kimwaga, Richard; Gabrielsson, Sara (Tanzania Journal of Engineering and Technology, 2019)
The use of High Rate Algal Ponds (HRAPs) for the treatment of wastewater and resource recovery has raised interest in recent years. Treatment of wastewater through this technology has proved to have high efficiency in reducing the level of pollution, nutrients, dissolved solids as well as pathogens. HRAPs are more efficient than conventional Wastewater Stabilization Ponds (WSPs) due to their design approach that provides room for high rate bio-chemical processes, which increase the mechanisms of nutrients and pathogens removal as well as the rate of micro-algae production for purposes of resource recovery. This paper reviews the upgrading potential of existing WSPs to HRAPs for resource recovery from products of wastewater for biofuel production, as a plant nutrient or for irrigation purposes and animal feeding. Several results have reported HRAPs to have efficiency in reducing bacterial contamination in excess of 99% while the removal of organic matter of up to 84% for Chemical Oxygen Demand (COD) and 88% for Biochemical Oxygen Demand under normal conditions have been reported. The removal for nitrogen was indicated to vary from 50 t0 98% while that of phosphorus varies from 32 to 99% depending on the culture conditions. It was further noted that, the potential for resource recovery from HRAPs is high in terms of energy and nutrients recovered through algae biomass, particularly for biofuel and animal feed production. Whereas among the dominant algal species of the HRAP Chlorella vulgaris revealed to have suitability in both treatment of wastewater and achieved a higher effluent quality and having nutrients contents essential for lipid extraction for biofuel and as a protein source for animal feeding which is largely attributed by their ability to grow very rapidly and to tolerate varieties of cultural conditions. To date, limited research attention has been given to studying the re-use potential of wastewater for irrigation purposes in Africa. Keywords: High rate algal ponds, Wastewater Treatment, Micro-algae, Resource Recovery.